Case report: Compound heterozygous NUP85 variants cause autosomal recessive primary microcephaly - Ravindran, Ethiraj; Lesca, Gaetan; Januel, Louis; Goldgruber, Linus; Dickmanns, Achim; Margot, Henri; Kaindl, Angela M. (Frontiers in Neurology, 2023)
Nucleoporin (NUP) 85 is a member of the Y-complex of nuclear pore complex (NPC) that is key for nucleocytoplasmic transport function, regulation of mitosis, transcription, and chromatin organization. Mutations in various nucleoporin genes have been linked to several human diseases. Among them, NUP85 was linked to childhood-onset steroid-resistant nephrotic syndrome (SRNS) in four affected individuals with intellectual disability but no microcephaly. Recently, we broaden the phenotype spectrum of NUP85-associated disease by reporting NUP85 variants in two unrelated individuals with primary autosomal recessive microcephaly (MCPH) and Seckel syndrome (SCKS) spectrum disorders (MCPH-SCKS) without SRNS. In this study, we report compound heterozygous NUP85 variants in an index patient with only MCPH phenotype, but neither Seckel syndrome nor SRNS was reported. We showed that the identified missense variants cause reduced cell viability of patient-derived fibroblasts. Structural simulation analysis of double variants are predicted to alter the structure of NUP85 and its interactions with neighboring NUPs. Our study thereby further expands the phenotypic spectrum of NUP85-associated human disorder and emphasizes the crucial role of NUP85 in brain development and function.